2022
DOI: 10.3390/ma15196614
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Polycarboxylate Superplasticiser and Protein Retarders in Cementitious Materials Containing Na- Montmorillonite: Effect of Addition Methods

Abstract: Polycarboxylate superplasticiser (PCE) is notably sensitive towards Na-Montmorillonite (Na-Mmt), an impurity generated from the manufacturing of concrete aggregate due to the chemical intercalation and poor surface adsorption. In order to improve the poor compatibility of PCE, the protein-based retarders were applied as the sacrificial agents, and its synergetic effects in cementitious materials containing Na-Mmt were investigated. The protein-based retarders were applied as the sacrificial agents and its syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…When assessing the effect of the organic substances that form DJM, it was found that the dead jellyfish mass also had surface-active properties. Based on the analyzed literature [28][29][30][31][32][33][34][35][36][37]55], the feasibility of using surfactants in concrete and concrete mixtures can be reflected in the form of an Ishikawa cause-and-effect diagram presented in Figure 18.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When assessing the effect of the organic substances that form DJM, it was found that the dead jellyfish mass also had surface-active properties. Based on the analyzed literature [28][29][30][31][32][33][34][35][36][37]55], the feasibility of using surfactants in concrete and concrete mixtures can be reflected in the form of an Ishikawa cause-and-effect diagram presented in Figure 18.…”
Section: Resultsmentioning
confidence: 99%
“…These types of plasticizers are adsorbed in particles of cement and microsilica, contributing to a significant increase in the workability of concrete. Also, studies [27][28][29][30] confirm that the introduction of additional components, such as methacrylic ester, aminosulfonic acid, protein retarder, hydroxypropyl methylcellulose, and others, into the composition of polycarboxylate superplasticizers helps to increase their effectiveness. No less popular are lignosulfonate-based plasticizing additives.…”
Section: Introductionmentioning
confidence: 95%
“…Although there are different evaluation methods for the measures to suppress the negative effects of clay, for XRD can intuitively reflect the changes in interlayer spacing of clay, and Zeta potential could also characterize the influence of organic compounds on clay potential. However, based on the differences in molecular weight and side chain functional groups of PCEs, the anti-clay performance and mechanism of different sacrificial agents may also vary (Alves et al, 2016;Li et al, 2018;Tian et al, 2022, Xu et al, 2016. There is still relatively insufficient research on how to further optimize the molecular structure of the sacrificial agents, matching the types and amounts of sacrificial agents corresponding to their performance.…”
Section: Introductionmentioning
confidence: 99%